Compensation Provisions in a Venture Capital-Limited Partner (VC-LP) Contract : A Theoretical Framework - Mishra, Sarita; Bag, Dinabandhu (Indian Journal of Finance, 2016)
In a venture capital (VC) deal, a partnership contract is designed to avoid different conflicts arising due to information asymmetry and agency problem and to make appropriate provision for compensation. This study investigated different theoretical approaches that have been deployed to understand this phenomenon. This article extracted the important aspects of the compensation structure and covenants required to set in the contract between venture capitalists and their limited partner (LP) in order to meet the agreed-upon proportion of return distribution and proposed a VC compensation model. Various studies were analyzed to get evidence on various aspects of a VC deal, such as the reasons why professional VCs exist, and factors that determine the design of a contract. Private ownership, information asymmetry, and illiquidity associated with a VC investment are key explanatory factors, which make VC - LP partnership agreement different from other financial contracts. The findings of this study could be alienated into two constituents. First, the compensation that a VC receives from its LP is performance based, which varies according to the size of the fund, experience of VC, past performance of VC, and signalling function. Second, some important covenants are generally mentioned in such a contract during raising funds for investments, though these are heterogeneous in each deal and their contribution in compensation allocation varies with each deal. In this study, we have proposed a compensation model for venture capitalists as a general partner by their limited partner, which is based on a principal-agent model. Also, this study focuses on contractual covenants, which are responsible for imparting flexible incentive provision and provide control over VC activity. The arrangement of VC compensation and covenants depend upon the management support and effort of VCs. This study can contribute to resolving the conflicts - between venture capitalists and their investors - that arise due to the agency problem and bring to light the compensation arrangement and provision of covenants used in the contract between VCs and their LPs.